2021
DOI: 10.3390/land10020227
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Regional Geographic Challenges: The Resilience of Chinese Vineyards to Land Degradation Using a Societal and Biophysical Approach

Abstract: Land degradation, especially soil erosion, is a societal issue that affects vineyards worldwide, but there are no current investigations that inform specifically about soil erosion rates in Chinese vineyards. In this review, we analyze this problem and the need to avoid irreversible damage to soil and their use from a regional point of view. Information about soil erosion in vineyards has often failed to reach farmers, and we can affirm that to this time, soil erosion in Chinese vineyards has been more of a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Thus, our framework for combining erosion monitoring and CADRs would allow land managers to have a better understanding of the quantitative target rate of erosion that can maintain good ecological status and halt or potentially reverse land degradation [127]. This research illustrates that a quantitative target of a natural background rate of erosion would be particularly useful when planning and managing different land uses such as vineyards [21,26,122,125,128], specific locations impacted by wildfire [33][34][35], and construction sites [22,24,33].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, our framework for combining erosion monitoring and CADRs would allow land managers to have a better understanding of the quantitative target rate of erosion that can maintain good ecological status and halt or potentially reverse land degradation [127]. This research illustrates that a quantitative target of a natural background rate of erosion would be particularly useful when planning and managing different land uses such as vineyards [21,26,122,125,128], specific locations impacted by wildfire [33][34][35], and construction sites [22,24,33].…”
Section: Discussionmentioning
confidence: 95%
“…Knowing just how much grazing, wildfire, and urbanization can increase soil erosion above natural rates has implications for the sustainable management of arid-region soils. The accelerated soil erosion by human activities is a major concern for land management with respect to soil degradation (e.g., [11,12,15,19,22,36,[121][122][123][124][125]). Through their extensive review of tolerable soil erosion rates for human society, Verheijen et al [126] concluded that soil functions can generally be maintained as long as soil erosion does not exceed natural erosion rates.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the quality and ecology of cultivated land have attracted attention from the government. Agricultural land degradation is often affected by the loss of soil fertility and biodiversity, which is commonly caused by unsustainable agricultural land management practices, such as longterm monoculture cropping (Chen S. et al, 2018;Chen et al, 2020;Yu and Jesús, 2021). In China, because of the limited area of cultivated land, the same crop is often continually grown in the same field without interruption, which typically leads to the continuous cropping (CC) obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the negative impacts of the erosion process, especially, in vineyards, it is necessary to estimate the risk of erosion and to identify the vulnerable areas for adequate territorial planning (Rodrigo‐Comino, 2018). However, numerous viticultural areas over the world remain unstudied, for example in China (Yu & Rodrigo‐Comino, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous viticultural areas over the world remain unstudied, for example in China (Yu & Rodrigo-Comino, 2021).…”
mentioning
confidence: 99%